2006
DOI: 10.1007/s10775-006-9001-8
|View full text |Cite
|
Sign up to set email alerts
|

Socio-cultural differences between Jewish and Arab teachers’ attitudes toward career education in Israel

Abstract: Teachers' attitudes towards career education play a crucial role in the successful implementation of relevant career related programs in school curriculum. In the current study, attitudes towards career education are investigated among 202 Israeli Arabs and 136 Israeli Jewish teachers. Results demonstrated similarity in the general pattern of ranking of importance of career education goals, but significant differences emerged in relation to a number of issues (e.g. self-knowledge, familiarity with range of occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“…It demonstrates that non-Western multicultural groups may actually have a deeper perception of autonomy in the context of caring for patients, as in the case of the Arab caretakers. Hence, contrary to the prevailing stance in the theoretical literature, according to which a smaller and lighter support for autonomy should be expected from such multicultural groups, and particularly the Arab population in Israel, 28 31,42 –44 our study showed that the Arab caretakers have a higher commitment to a full-fledged autonomy of the patient, in comparison with the Sabras. 31 34,45 –47 Indeed, in the next section, we shall offer an explanation to this interesting finding, based on connecting the findings regarding the particular emphasis that Arab caretakers place on the idea of “person-centered care” and their support for a more comprehensive conceptualization of the autonomy of their patients.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…It demonstrates that non-Western multicultural groups may actually have a deeper perception of autonomy in the context of caring for patients, as in the case of the Arab caretakers. Hence, contrary to the prevailing stance in the theoretical literature, according to which a smaller and lighter support for autonomy should be expected from such multicultural groups, and particularly the Arab population in Israel, 28 31,42 –44 our study showed that the Arab caretakers have a higher commitment to a full-fledged autonomy of the patient, in comparison with the Sabras. 31 34,45 –47 Indeed, in the next section, we shall offer an explanation to this interesting finding, based on connecting the findings regarding the particular emphasis that Arab caretakers place on the idea of “person-centered care” and their support for a more comprehensive conceptualization of the autonomy of their patients.…”
Section: Discussioncontrasting
confidence: 96%
“…These assumptions are grounded on previous research, both in medical ethics and in cultural studies. [31][32][33][34]…”
Section: Methodsmentioning
confidence: 99%
“…In the Arabic sector, the possibility to pose demands on teachers is much easier since as a relatively conservative society, it is more customary to follow the principal's orders on these issues. Secondly, because of a feeling of discrimination and the awareness of gaps between both sectors, the notion among Arab principals is that teacher training on these ICT‐related issues is essential for advancing education in Arab‐speaking schools (Khattab 2003; Flum & Cinamon 2006).…”
Section: Resultsmentioning
confidence: 99%
“…ethnic, religious and national). It has been argued, however, that the greatest heterogeneity is found between the Jewish majority and the Arab minority (Al‐Haj, ; Bauman, ; Flum and Cinamon, ; Sagy, Orr & Bar‐On, ; Triandis, ). The Muslim Arab minority in not only differs from the Jewish majority in religion, language and culture, is also perceived as a ‘hostile minority’ and thus exposed to various forms of discrimination that significantly impede their members’ successful socioeconomic integration in Israeli society (Ayalon and Sagy, ).…”
Section: The Israeli Contextmentioning
confidence: 99%